Self-assessment of Schools. Reflection on the Improvement of the Educational System - José Filipe Correia Esteves (Universidad Autónoma de Madrid, 2015)
This article reflects on the system of self-assessment and its potential contribution to the improvement of educational practices. To this end, we prepared a single case study in a primary and secondary school in the municipality of Câmara de Lobos in the Autonomous Region of Madeira. The data collection techniques applied were the semi-structured interview, natural and participant observation and document analysis. Content analysis and triangulation were used to analyse and interpret the results. It was verified that the school under study does not apply the European model CAF (Common Assessment Framework), but it has an internal evaluation team that does all the qualitative and statistical processing of various data, from student outcomes, to the level of efficiency of educational services, among others. So the school implements an open and flexible system of self-assessment. However, this school evaluation system does not allow the detection of its weaknesses and its strong areas, which might enable the creation of improvement plans, and ultimately allow the school to be better able to meet the challenge of a possible external assessment. We conclude that the implementation of a quality management model in a school should be based on clearly outlined objectives, which takes into account the school's particular universe and is actually feasible. To this end, the school must adopt observation and analysis instruments that will contribute to a diagnostic that in due course will help perfect practices and improve the educational system.